Mid-IR hyperspectral imaging for label-free histopathology and cytology. (24th January 2018) - Hermes, M; Morrish, R Brandstrup; Huot, L; Meng, L; Junaid, S; Tomko, J; Lloyd, G R; Masselink, W T; Tidemand-Lichtenberg, P; Pedersen, C; Palombo, F; Stone, N
Abstract: Mid-infrared (MIR) imaging has emerged as a valuable tool to investigate biological samples, such as tissue histological sections and cell cultures, by providing non-destructive chemical specificity without recourse to labels. While feasibility studies have shown the capabilities of MIR imaging approaches to address key biological and clinical questions, these techniques are still far from being deployable by non-expert users. In this review, we discuss the current state of the art of MIR technologies and give an overview on technical innovations and developments with the potential to make MIR imaging systems more readily available to a larger community. The most promising developments over the last few years are discussed here. They include improvements in MIR light sources with the availability of quantum cascade lasers and supercontinuum IR sources as well as the recently developed upconversion scheme to improve the detection of MIR radiation. These technical advances can substantially speed up data acquisition of multispectral or hyperspectral datasets thus providing the end user with vast amounts of data when imaging whole tissue areas of many mm 2 . Therefore, effective data analysis is of tremendous importance, and progress in method development is discussed with respect to the specific biomedical context.